High‐Resolution 3‐D Imaging of Daytime Sporadic‐E Over Japan by Using GNSS TEC and Ionosondes - Weizheng Fu; Nicholas Ssessanga; Tatsuhiro Yokoyama; Mamoru Yamamoto (Space Weather)
Abstract A novel two‐step three‐dimensional (3‐D) computerized ionospheric tomography (CIT) technique has been developed to image the structure of daytime midlatitude sporadic‐E (Es). The CIT relies on total electron content (TEC) from a dense ground‐based Global Navigation Satellite System (GNSS) receiver network over the Japan area. First, on a coarse grid, the TEC data and a multiplicative algebraic reconstruction technique (MART) are used to reconstruct the F region from a smooth background. Then, on a fine grid and using singular value decomposition (SVD), the residues after deducting the F region contribution to TEC are utilized in reconstructing the E region, extending 80–180 km in altitude. To vertically constrain the E region solution, we introduced a family of subsets of time‐dependent empirical orthogonal functions (EOFs) from a Chapman model function tuned to manually scaled ionosonde observations. We analyzed three event days to validate the results. East‐West (E‐W) aligned frontal structures, spanning several hundred kilometers, migrating northward in the morning and southward in the afternoon, were observed. The new technique effectively tracks the Es‐height variation over time, which had proved difficult to reproduce in earlier tempts at 3‐D Es reconstructions.